DETERMINING THE PRICE OF AGRICULTURAL PRODUCTS IN THE REVIEW OF SHARIAH ECONOMIC LAW (STUDY OF THE VILLAGE CIMPAGO MARKET IN PARIAMAN) - Daipon, Dahyul; Putri, Yulinda Dewi; Hendri, Hendri; Bustamar, Bustamar (JURNAL HAKAM, 2023)
Review of Islamic Law Regarding the Setting of the Selling and Buying Prices of Agricultural Products at the Nagari Campago Market in District V Koto Kampung Dalam, Padang Pariaman Regency, is the topic of this thesis. The writers of this publication combine library research with a form of outdoor research. where information is gathered via documentation, interviews, and observation. Permanent traders and migrant traders (urang darek) serve as the study's main sources of information. Based on the study's findings, it can be concluded that price fixing mechanism is carried out by permanent traders in Nagari Campago, namely by seeking information regarding prices that are based on other markets, besides that regular traders are also based on the previous market price. Not only that, in addition to being based on market prices on the previous Sunday, traders still apply prices from migrant traders, in the sense that traders still take goods from migrant traders A, but traders still ask the selling price of goods to newcomer traders B. Muamalah Fiqh's view regarding the determination of buying and selling prices for agricultural products that occurs at the Nagari Campago Market, V Koto Kampung Dalam District has become an Urf which means something that is no longer foreign to a community because it has become a habit and is integrated into their lives in the form of actions and words.